2007
DOI: 10.1029/2005tc001872
|View full text |Cite
|
Sign up to set email alerts
|

Early exhumation of high‐pressure rocks in extrusion wedges: Cycladic blueschist unit in the eastern Aegean, Greece, and Turkey

Abstract: Structural, metamorphic, and geochronologic work shows that the Ampelos/Dilek nappe of the Cycladic blueschist unit in the eastern Aegean constitutes a wedge of high-pressure rocks extruded during early stages of orogeny. The extrusion wedge formed during the incipient collision of the Anatolian microcontinent with Eurasia when subduction and deep underthrusting ceased and the Ampelos/Dilek nappe was thrust southward over the greenschist-facies Menderes nappes along its lower tectonic contact, the Cycladic-Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 83 publications
5
126
0
Order By: Relevance
“…The geochronological data indicate that the top-to-the-WSW thrust at the base of the Styra Nappe operated, within errors, at the same time as the topto-the-ENE normal fault at the top of the Styra Nappe. This conclusion is corroborated by the gradual reversal of the shear-sense data from top-to-the-WSW in the basal Styra Nappe to top-to-the-ENE in the upper Styra Nappe; there are no systematic cross-cutting relationships between the fabrics (Ring et al 2007a).…”
Section: Aegean Sea Examples Of Extrusion Wedgessupporting
confidence: 65%
See 3 more Smart Citations
“…The geochronological data indicate that the top-to-the-WSW thrust at the base of the Styra Nappe operated, within errors, at the same time as the topto-the-ENE normal fault at the top of the Styra Nappe. This conclusion is corroborated by the gradual reversal of the shear-sense data from top-to-the-WSW in the basal Styra Nappe to top-to-the-ENE in the upper Styra Nappe; there are no systematic cross-cutting relationships between the fabrics (Ring et al 2007a).…”
Section: Aegean Sea Examples Of Extrusion Wedgessupporting
confidence: 65%
“…Shaked et al (2000) and Ring & Layer (2003) showed that the Styra Nappe was thrust onto the Basal Unit during top-to-the-WSW shortening. Ring et al (2007a) dated mylonites resulting from this process at 29.5 ± 0.3 Ma. This age is similar to the 40 Ar-39 Ar white mica ages from thrust-related mylonites of c. 35-30 Ma of Ring & Layer (2003).…”
Section: Aegean Sea Examples Of Extrusion Wedgesmentioning
confidence: 99%
See 2 more Smart Citations
“…Butler and Freeman, 1996) and vertical ductile thinning (Ring and Kassem, 2007) (Figure 11b). The extrusion wedge model has been shown as a viable exhumation mechanism for high-pressure rocks in the Aegean Sea region and the Tauern Window of the Eastern Alps (Ring et al, 2007a;Ring et al, 2007b;Ring and Glodny, 2010). It demands alternating shear sense across the extruding wedge, i.e.…”
Section: Exhumation Of the Gran Paradiso Massifmentioning
confidence: 99%